(untitled) (Mustansiria Dental Journal, 2018)
Background: Polycystic ovary syndrome (PCOS) is the most common endocraniopathy in women of reproductive age, affecting (5-10) % of population and it is the leading cause of female infertility. C-reactive protein CRP, is a member of a group of acute phase of protein which increase their concentrations during certain inflammation disorders and used as a biomarker of inflammation in the body. Aim of the study: is to assess the salivary level of CRP with were oral disease was stimulated by evaluate gingival inflammation, plaque accumulation in some Iraqi women with PCOS disease in compared with women not have PCOS. Methods: 19 females with PCOS and 26 females with systemically healthy include in this study. Saliva were collected and CRP were examined and evaluated by using ELISA method in both study and control group. For all groups we examine the oral inflammation was measured depending on gingival and plaque index. Results: the results reported all PCOS women have significant increase in the salivary CRP than women with no PCOS) mean ± SD (226.8±34SD, 173.8±22.5 respectively). All women with PCOS had significantly increased in gingivitis than with no PCOS women. Conclusion: An increase in salivary CRP and gingival inflammation were found in women with PCOS. Also suggested measurement of salivary CRP may be helpful in predicting women with oral disease in PCOS women.